Citrulline Supplementation Improves Organ Perfusion and Arginine Availability under Conditions with Enhanced Arginase Activity - Wijnands, Karolina A.P. (Nutrients, 2015)
Enhanced arginase-induced arginine consumption is believed to play a key role in the pathogenesis of sickle cell disease-induced end organ failure. Enhancement of arginine availability with l-arginine supplementation exhibited less consistent results; however, l-citrulline, the precursor of l-arginine, may be a promising alternative. In this study, we determined the effects of l-citrulline compared to l-arginine supplementation on arginine-nitric oxide (NO) metabolism, arginine availability and microcirculation in a murine model with acutely-enhanced arginase activity. The effects were measured in six groups of mice (n = 8 each) injected intraperitoneally with sterile saline or arginase (1000 IE/mouse) with or without being separately injected with l-citrulline or l-arginine 1 h prior to assessment of the microcirculation with side stream dark-field (SDF)-imaging or in vivo NO-production with electron spin resonance (ESR) spectroscopy. Arginase injection caused a decrease in plasma and tissue arginine concentrations. l-arginine and l-citrulline supplementation both enhanced plasma and tissue arginine concentrations in arginase-injected mice. However, only the citrulline supplementation increased NO production and improved microcirculatory flow in arginase-injected mice. In conclusion, the present study provides for the first time in vivo experimental evidence that l-citrulline, and not l-arginine supplementation, improves the end organ microcirculation during conditions with acute arginase-induced arginine deficiency by increasing the NO concentration in tissues.